2010
DOI: 10.1016/j.marpetgeo.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of gas hydrate formation and destabilisation using a novel high-pressure apparatus

Abstract: a b s t r a c tA novel variable-volume type high-pressure apparatus has been designed, constructed and used for gas hydrate investigations. The apparatus has an operating temperature ranging from 253 K to 473 K and pressure ranging from 0.1 MPa to 60 MPa. Its central component consists of a viewing windows cell to which several sensors or analytical instruments can be connected. At its present configuration, a Raman spectrometer and a gas chromatograph are connected for the study of the liquid (or solid) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The phase equilibrium experiments were performed with the apparatus described by Ruffine et al [42], which was modified to accommodate a high-pressure stirrer (minimaster, Premex Reactor AG, Lengnau, Switzerland) ( Figure 2). It consists of a cylindrical 316Ti variable-volume high-pressure cell with a 17-4PH stainless steel moving piston (Hand-Operated Pressure Generator with optical cell, SITEC-Sieber Engineering AG, Maur, Switzerland).…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The phase equilibrium experiments were performed with the apparatus described by Ruffine et al [42], which was modified to accommodate a high-pressure stirrer (minimaster, Premex Reactor AG, Lengnau, Switzerland) ( Figure 2). It consists of a cylindrical 316Ti variable-volume high-pressure cell with a 17-4PH stainless steel moving piston (Hand-Operated Pressure Generator with optical cell, SITEC-Sieber Engineering AG, Maur, Switzerland).…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…This might be because high pressure at 1.9 MPa changed in the structure of the fresh-cut samples that led to increased metabolisms (Perera, Gamage, Wakeling, Gamlath, & Versteeg, 2010;Rastogi, 2010). According to previous studies Ando et al, 2009;Ruffine et al, 2010;Wu et al, 2012), suppression of the respiration rate in fresh-cut samples treated with high-pressure N 2 might be due to dissolution of N 2 into intracellular water in samples, resulting in reduction of enzyme activities and fluidity of intracellular water, and thereby slowing down the metabolism.…”
Section: Effect Of Pressurized N 2 On Respiration Ratementioning
confidence: 94%
“…Nowadays, gas-based food preservation technology has been preferably used to preserve quality of fresh-cut fruits (Wu & Zhang, 2011).When gases such as xenon and nitrogen are dissolved in water under appropriately selected temperature and pressure condition, water molecules form a cage of polyhedral structure that can hold gas molecules, known as the clathrate hydrate (Chatti, Delahaye, Fournaison, & Petitet, 2005;Linga, Kumar, & Englezos, 2007;Anderson, 2007;Disalvo et al, 2008;Zhang, Zhan, Wang, & Tang, 2008;Ando et al, 2009;Ruffine, Donval, Charlou, Cremière, & Zehnder, 2010;Wu, Zhang, & Adhikari, 2012).Some studies suggested that mobility of water in fruits and vegetables can be greatly restricted due to the formation of clathrate hydrate (Zhan, 2005;Meng, Zhang, Zhan, & Adhikari, 2013). The method of structured water was effective in extending vase life of cut carnations treated with Xe (Oshita, Seo, Kawagoe, Koreeda, & Nakamura, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A sample of crystalline methane hydrate is shown in Figure 5. The experimental work conducted by Ruffine et al showed that when the pressure and temperature in the gas hydrate system are increase, and if the ice structure surrounding the hydrate is stable to some extent, the methane hydrate will have larger pressure than the ice phase [15]. Their experiment depicted the function of the hydrate skin, somewhat, as a barrier, and the effect of breaking that barrier on the kinetics of the hydrate-ice structure in a closed system.…”
Section: Gas Hydratementioning
confidence: 99%